A Cross-National Investigation of Cultural Representations in Iranian and Turkish ELT Coursebooks - Dolgunsöz, Emrah; YİĞİT, Monireh Azimzadeh (LPPM Universitas Advent Indonesia, 2022)
Acquiring second/foreign language competence inherits target culture knowledge and awareness. In this regard, English Language Teaching (ELT) coursebooks play a significant role in culture acquisition especially in an English as a foreign language (EFL) context in which learners have little or no opportunity to practice English outside the classroom. Therefore, the purpose of this study was to investigate and compare the cultural content of local EFL textbooks used in two Muslim countries; Iran and Turkey. Kachru’s concentric model was used to explore cultural contents of Iranian and Turkish 9th grade EFL coursebooks and the data was analyzed through content analysis. Results showed that the Iranian coursebook was vastly filled with native culture along with a few subjects from expanding circle countries such as Russia and China. On the other hand, the main cultural focus of the Turkish EFL coursebook was inner-circle countries while little emphasis was made on native culture. The results were discussed in terms of intercultural competence and material design in the EFL context.